Harnessing The Theory of Discovery to Enhance Project-Based Learning of Pupils in Primary Schools (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The primary school pupil is a child that is yearning for learning and exploration of the environment. Due to children’s curiosity and inquisitiveness at this level, there are needs to use appropriate learning methods that can actually lead children to explore their environment. Despite the fact that pupils are supposed to enjoy the learning process, there seem to be a breach in pupils’ interest. This loss of interest has manifested in pupils making noise during lesson, withdrawal from participating in classroom discussion. This paper therefore proposed that, if project-based learning is used as a method of teaching in primary school, the principles of doing as prescribed by theory of discovery will be harnessed and pupils will learn better. In the course of the discussion, this paper outlined practical ways of using project-based learning to harness the theory of discovery which include; use of open-ended questions that provoke inquiry and curiosity, creating resource-rich environment for children to explore, and connecting projects to real-life context among others. The paper further implied that, classroom activities should include tasks involving tangible materials or tools to encourage exploration and sensory engagement among children. It was however suggested in this paper that, to harness the theory of discovery and enhance project-based learning, caregivers should be equipped with skills to design open-ended enquiry-driven projects, that allow children explore, hypothesize and experiment through training programmes; initiate projects that are relevant to pupils’ experiences, interest and local environment among others.